2015
DOI: 10.5380/avs.v20i2.36390
|View full text |Cite
|
Sign up to set email alerts
|

Influência Do Enriquecimento Ambiental Nos Padrões De Comportamentos Sociais E Anormais De Cabras Em Confinamento

Abstract: RESUMO:A partir do processo de domesticação as cabras foram retiradas do seu ambiente natural e inseridas em um ambiente empobrecido em estímulos. O problema é que, em função do confinamento inadequado, os animais deixam de realizar comportamentos típicos da espécie e passam a desenvolver comportamentos anormais. Na tentativa de minimizar esses comportamentos, têm-se utilizado a técnica denominada enriquecimento ambiental. O objetivo do trabalho foi identificar, analisar e descrever os comportamentos sociais a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The results of our study were similar to those reported by Oliveira et al, (2015) and Almeida, Margarido and Monteiro Filho (2008). They observed behavioral changes in feed-lot animals with the enrichment of their ambient because this practice makes the environment more comfortable and reduces the apathy in feed-lot animals.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our study were similar to those reported by Oliveira et al, (2015) and Almeida, Margarido and Monteiro Filho (2008). They observed behavioral changes in feed-lot animals with the enrichment of their ambient because this practice makes the environment more comfortable and reduces the apathy in feed-lot animals.…”
Section: Resultssupporting
confidence: 93%
“…The behavior of biting stall parts alternated with food intake was considered abnormal and recorded as stereotyped behavior, as well as licking several times the same spot or standing without moving in front of the wall in the same place for a long time. Oliveira et al (2015) stated that goats in feed-lot in environmentally not appropriate places tend to show abnormal behaviors, such as stereotypy, self-destruction, and depraved appetite among others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Divulga-se muito o bem-estar animal associado principalmente a qualidade da carne bovina (OLIVEIRA; BORTOLI; BARCELLOS, 2008). Em cabras em confinamento, por sua vez, a introdução de técnicas de enriquecimento ambiental diminuiu a incidência de comportamentos agonísticos e anormais, melhorando efetivamente a qualidade de vida destes animais (OLIVEIRA et al, 2015).…”
Section: Metodologiaunclassified